Front Cover: Positive Cooperativity Induced by Interstrand Interactions in Silver(I) Complexes with α, α′‐Diimine Ligands (Chem. Eur. J. 42/2022). Issue 42 (4th July 2022) - Zare, Davood; Piguet, Claude; Prescimone, Alessandro; Housecroft, Catherine E.; Constable, Edwin C.
Abstract : Because of its large size and its optimized covalency toward heterocyclic N‐donor atoms, the intermediate [Ag I L ] + unit (depicted as a paraglider) is eager to catch a second α, α'‐diimine ligands coming down from the summit of positive allosteric coperativity. The final stable [Ag I L 2 ] + complex reaches the Valley of Stability. More information can be found in the Research Article by D. Zare, C. Piguet, E. C. Constable et al. (DOI: 10.1002/chem.202200912 ).